Institutional Forces and Environmental Management Strategy: Moderating Effects of Environmental Orientation and Innovation Capability. (29th June 2018) - Kang, Yuanfei; He, Xinming
ABSTRACT: We examine the mechanisms through which firm capabilities moderate the impact of institutional forces upon firms' adoption of environmental management strategy (EMS). Viewing the limitations of the institutional perspective in explaining the heterogeneity in firms' EMS, we suggest that an important source of variation is the idiosyncratic capabilities of the firm in acquiring and allocating resources. Based on the strategic response theme of institutional theory and the resource-based view, we argue that the influence of institutional forces on EMS is contingent on the presence of environmental orientation and innovation capability. Using data collected from China, we test these notions. Our empirical results suggest that both environmental orientation and innovation capability positively moderate the effect of institutional forces on firm's EMS. By demonstrating how institutional forces and firm capabilities interact with each other, we enhance our understanding of how firms succeed in developing EMS.